TRANSFORMING HEALTHCARE IN PAKISTAN - AHMAD, M (Biological and Clinical Sciences Research Journal, 2024)
Pakistan, a country facing significant healthcare challenges, is witnessing a transformation through the efforts of the Pakistan Employees Social Security Institution (PESSI). This article explores the pivotal role of PESSI in providing comprehensive healthcare and social security to low-income workers and their families. Highlighting the achievements of the Rahmatul-lil-Alameen Institute of Cardiology (RAIC), the article underscores the institution’s impact on improving health outcomes and social support in Pakistan